Optical klystron FEL scheme for x-ray coherent harmonic generation at ISLF storage ring - A raghavi; H R Shfeghat; M R Benam (Iranian Journal of Physics Research, 2019)
The possibility of inserting an optical klystron on the storage ring of an Iranian Light Source Facility as a Synchrotron Radiation Free electron Laser for coherence harmonic generation in the soft x-ray spectrum has been studied. The study has been performed using the 3D FEL simulation code GENESIS 1.3 and in accordance with the available characteristic parameters of ISLF. Different potential schemes together with their output and characteristics are discussed.